A Comment on Mean-Variance Portfolio Selection with Either a Singular or a Non-Singular Variance-Covariance Matrix - Ryan, Peter J.; Lefoll, Jean (Journal of Financial and Quantitative Analysis, 1981)
Peter J. Ryan, Jean Lefoll, A Comment on Mean-Variance Portfolio Selection with Either a Singular or a Non-Singular Variance-Covariance Matrix, The Journal of Financial and Quantitative Analysis, Vol. 16, No. 3 (Sep., 1981), pp. 389-395